Traumatic Cervical Artery Dissection and Ischemic Stroke: Anticoagulation or Antiplatelet Therapy? The Controversies Remain - Welling, Leonardo Christiaan; Fukuda, Camila Mariana; da Luz, Edek Francisco de Mattos; Welling, Mariana Schumacher; Figueiredo, Eberval Gadelha (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2015)
Arterial dissection of the wall of the carotid artery is a recognized and significant cause of stroke. We described a 22-year-old man presented to the emergency department after a motorcycle accident. He had a right acetabular fracture and had not complained of other symptoms. A few minutes after being admitted, the patient developed left side hemiparesis. Emergency brain magnetic resonance imaging (MRI) revealed an acute ischemia in the left basal ganglia. Conventional angiography confirmed almost complete occlusion of carotid artery lumen. We treated the patient with antiplatelet therapy and he is currently followed at the outpatient clinic with good recovery of motor symptoms. Early identification and management of cervical artery dissection is important, as it is one of the major causes of ischemic stroke in young adults. Despite previous published articles, the best treatment of carotid artery dissection, especially after trauma, remains controversial.
Keywords: ischemia; carotid artery; dissection